Optimizing training programs for athletic performance: a Monte-Carlo Tree Search variant method - Houy, N. (MedRxiv The preprint server for health sciences, 2020)
Purpose: Using a variant of the Monte-Carlo Tree Search (MCTS) algorithm, we compute optimal personalized and generic training programs for athletic performance.